A cosmic jet swinging our way. (January 2018) - Meyer, Eileen T.
Long-term multi-wavelength monitoring of a jet from a supermassive black hole reveals that more intense periods of variability in brightness occur when the jet is pointed more directly at Earth, thereby strengthening the geometric interpretation of long-term changes in brightness.